English-Pangutaran Sama dictionary - Walton, Janice; Walton, Charles; Summer Institute of Linguistics (Philippines). (Manila Summer Institute of Linguistics-Philippines, 1992)
A helpful reference for Pangutaran speaking students in their study of the English language. Contains synonyms, root words and affixes, sample sentences and an index of Pangutaran words.
Published in cooperation with the Commission on Philippine Languages and the Department of Education, Culture and Sports.
Keywords: English language -- Pangutaran Sama. -- Dictionaries; Pangutaran Sama language -- Glossaries, vocabularies, etc; Pangutaran Sama language -- Sentences